A Comparison of Iron Oxide Particles and Silica Particles for Tracking Organ Recellularization - Joseph E. Kobes MS; George I. Georgiev MS; Anthony V. Louis MD; Isen A. Calderon PhD; Eriko S. Yoshimaru PhD; Louie M. Klemm MS; Douglas W. Cromey MS; Zain Khalpey MD, PhD; Mark D. Pagel PhD (Molecular Imaging)
Reseeding of decellularized organ scaffolds with a patient’s own cells has promise for eliminating graft versus host disease. This study investigated whether ultrasound imaging or magnetic resonance imaging (MRI) can track the reseeding of murine liver scaffolds with silica-labeled or iron-labeled liver hepatocytes. Mesoporous silica particles were created using the Stöber method, loaded with Alexa Flour 647 fluorophore, and conjugated with protamine sulfate, glutamine, and glycine. Fluorescent iron oxide particles were obtained from a commercial source. Liver cells from donor mice were loaded with the silica particles or iron oxide particles. Donor livers were decellularized and reperfused with silica-labeled or iron-labeled cells. The reseeded livers were longitudinally analyzed with ultrasound imaging and MRI. Liver biopsies were imaged with confocal microscopy and scanning electron microscopy. Ultrasound imaging had a detection limit of 0.28 mg/mL, while MRI had a lower detection limit of 0.08 mg/mL based on particle weight. The silica-loaded cells proliferated at a slower rate compared to iron-loaded cells. Ultrasound imaging, MRI, and confocal microscopy underestimated cell numbers relative to scanning electron microscopy. Ultrasound imaging had the greatest underestimation due to coarse resolution compared to the other imaging modalities. Despite this underestimation, both ultrasound imaging and MRI successfully tracked the longitudinal recellularization of liver scaffolds.